solve for x:
(x-5)/10 -(x-3)/2 = 8+x
Answers
Answered by
12
Solution :
(x-5)/10 - (x-3)/2 = 8+x
=>[x-5-5(x-3)]/10 = 8+x
=> ( x - 5 - 5x + 15 )= 10(8+x)
=> -4x + 10 = 80 + 10x
=> -4x-10x = 80 - 10
=> -14x = 70
=> x = 70/(-14)
=> x = -5
••••
Answered by
5
Refer to the attachment buddy..☺
___________❤
Attachments:
![](https://hi-static.z-dn.net/files/d4d/e0a4ed5536c93db36496c1fe40c60d72.jpg)
Similar questions
Computer Science,
8 months ago
Economy,
8 months ago
Math,
1 year ago
Math,
1 year ago
Math,
1 year ago